Visions of precarity in Japanese popular culture and literature - Iwata-Weickgenannt, Kristina; Rosenbaum, Roman; Römer, Maria (Routledge contemporary Japan series, 2015)
"Recent natural as well as man-made cataclysmic events have dramatically changed the status quo of contemporary Japanese society, and following the Asia-Pacific war's never-ending 'postwar' period, Japan has been dramatically forced into a zeitgeist of saigo or 'post-disaster.' This radically new worldview has significantly altered the socio-political as well as literary perception of one of the world's former superpowers, and in this book the contributors closely examine how Japan's new paradigm of precarious existence is expressed through a variety of pop-cultural as well as literary media. Addressing the transition from post-war to post-disaster literature, this book examines the rise of precarity consciousness in Japanese socio-cultural discourse. The chapters investigate the extent to which we can talk about the emergence of a new literary paradigm of precarity in the world of Japanese popular culture, and analysis of a variety of contemporary texts from literature, manga and anime, television drama and film offers an interpretation of the many dissonant voices in Japanese society. The contributors also outline the related social issues in Japanese society and culture, providing a comprehensive overview of the global trends that link Japan with the rest of the world. Visions of Precarity in Japanese Popular Culture and Literature will of great interest to students and scholars of contemporary Japan, Japanese culture and society, popular culture and social and cultural history"--